Persepsi Pengunjung Terhadap Fasilitas Daya Tarik Wisata Puncak Bukit Cambai Kabupaten Solok - Ananda Ikhlas Aldean; Retnaningtyas Susanti (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
This research was motivated by the inadequacy of main facilities, supporting facilities and supporting facilities on Cambai Hilltop Tourism Solok Regency. This study aims to determine and describe Visitor Perceptions of Cambai Hilltop Tourism Attraction Facilities. This type of research uses qualitative descriptive research. The study population used a purposive sample that focused on selected informants. Research informants consisted of 3 visitors, 1 manager and 1 community member. Data was collected through interviews and observations. The steps of analyzing data are data collection, data reduction, data presentation and conclusions. The results showed that the facilities of the Puncak Bukit Cambai Tourism Attraction of Solok Regency consisted of main facilities, supporting facilities and supporting facilities. The main facilities at the Cambai Hilltop Tourism Attraction are quite good. Supporting facilities at the Puncak Bukit Cambai tourist attraction are quite satisfactory, the supporting facilities at the Puncak Bukit Cambai tourist attraction are not satisfactory as seen from the condition of the toilet of the Puncak Bukit Cambai tourist attraction is still in a state of uncleanliness because it is still in the renovation stage. The condition of the parking lot is narrow, so the number of vehicles parked is limited and there is no vehicle protection such as the roof in the parking area. Access to the tourist attraction of Puncak Bukit Cambai is still not good.